(3GdJgQH GdVQjHj h GdGbJUGO GdGShO (B/s - (3GdTQbGhj, YHO GdMcje eUWais ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2006)
(3GdGbJUGO GdGShO (B((3eagheg(B- (3MLeg(B- (3GSHGH fehg(B) (3WQb JbOjQ MLe GdGbJUGO GdGShO GVGaI Gdi ebGQfI fJGFL WQb JbOjQ MLe GdGbJUGO GdGShO h cPG GdeTGQcI aj GdShb GdGShO(B, (3fJGFL GdJgQH GdVQjHj h GdGbJUGO GdGShO h aj GdGNjQ SjGSI GdehGLgI(B.s
(3eQGLY U(B.234s
Keywords: (3GdGbJUGO (B- (3VQGFHs; (3GdGbJUGO GdGShOs; (3GdVQGFH (B- (3JgQHs